Evidence-based decision-making for a public health emergency in china: Easier said than done - Zhand, L., Chen, K. and Zhao, Ji (American Review of Public Administration)
This article aims to argue that evidence-based decision-making for a public health emergency is (3z(Beasier said than done(3y (Breflected on COVID-19 response in China. For the local government, the behavioral pattern is prone to blame-avoiding instead of making decision following scientific evidence and experts$1 (Badvice. However, such behavior is not based on completely subjective judgment but a rational choice for the local government. Some consequences associated with China$1 (Bs response to COVID-19 reveals an inflexible administrative system. Therefore, China$1 (Bs governance reform should focus on empowering local governments with more flexibility and resilience, which enables los
Keywords: Evidence-based decision-making, Public health policy, local government, COVID-19, China